Pengelolaan Keuangan Desa Ditinjau Dari Undang-Undang Desa Menuju Masyarakat Yang Mandiri - Betha Rahma Sari (Universitas Islam Indonesia, 2020)
The background of this research is the guarantee of recognition of the existence of the village through the formation of Law Number 6 of 2014 on Villages (Village Law). The Village Government has a strategic role and position in public services and empowerment of the community. Therefore, in order to empower the community and carry out service functions, the village must be empowered in any sector, one of which is the village financial management. This research will answer the formulation of the problem regarding what is the benchmark in the success of the village financial management in terms of village-related laws and regulations so that a prosperous and independent society is created? This is a normative juridical research with a statutory regulatory approach. The results of the study concluded that the affirmative policy of Law Number 6 of 2014 on Villages has a positive effect on the effectiveness of village governance. This is shown by the increase in the effectiveness of Village government organizations and the effectiveness of village deliberations. In terms of economic independence, efforts to strengthen village financing capacity can be seen from the widening of access to funding resources. The opportunity to empower the village can be made more possible through the empowerment of village-owned enterprises and village cooperation with other villages and / or cooperation with third parties.